summary |
shortlog |
changelog |
graph |
tags |
bookmarks |
branches |
files |
changeset |
file |
latest |
revisions |
annotate |
diff |
comparison |
raw |
help

src/HOL/Isar_Examples/Hoare_Ex.thy

author | wenzelm |

Sat, 07 Apr 2012 16:41:59 +0200 | |

changeset 47389 | e8552cba702d |

parent 46622 | 3ccecb301d4e |

child 55656 | eb07b0acbebc |

permissions | -rw-r--r-- |

explicit checks stable_finished_theory/stable_command allow parallel asynchronous command transactions;
tuned;

header {* Using Hoare Logic *} theory Hoare_Ex imports Hoare begin subsection {* State spaces *} text {* First of all we provide a store of program variables that occur in any of the programs considered later. Slightly unexpected things may happen when attempting to work with undeclared variables. *} record vars = I :: nat M :: nat N :: nat S :: nat text {* While all of our variables happen to have the same type, nothing would prevent us from working with many-sorted programs as well, or even polymorphic ones. Also note that Isabelle/HOL's extensible record types even provides simple means to extend the state space later. *} subsection {* Basic examples *} text {* We look at few trivialities involving assignment and sequential composition, in order to get an idea of how to work with our formulation of Hoare Logic. *} text {* Using the basic @{text assign} rule directly is a bit cumbersome. *} lemma "|- .{\<acute>(N_update (\<lambda>_. (2 * \<acute>N))) : .{\<acute>N = 10}.}. \<acute>N := 2 * \<acute>N .{\<acute>N = 10}." by (rule assign) text {* Certainly we want the state modification already done, e.g.\ by simplification. The \name{hoare} method performs the basic state update for us; we may apply the Simplifier afterwards to achieve ``obvious'' consequences as well. *} lemma "|- .{True}. \<acute>N := 10 .{\<acute>N = 10}." by hoare lemma "|- .{2 * \<acute>N = 10}. \<acute>N := 2 * \<acute>N .{\<acute>N = 10}." by hoare lemma "|- .{\<acute>N = 5}. \<acute>N := 2 * \<acute>N .{\<acute>N = 10}." by hoare simp lemma "|- .{\<acute>N + 1 = a + 1}. \<acute>N := \<acute>N + 1 .{\<acute>N = a + 1}." by hoare lemma "|- .{\<acute>N = a}. \<acute>N := \<acute>N + 1 .{\<acute>N = a + 1}." by hoare simp lemma "|- .{a = a & b = b}. \<acute>M := a; \<acute>N := b .{\<acute>M = a & \<acute>N = b}." by hoare lemma "|- .{True}. \<acute>M := a; \<acute>N := b .{\<acute>M = a & \<acute>N = b}." by hoare simp lemma "|- .{\<acute>M = a & \<acute>N = b}. \<acute>I := \<acute>M; \<acute>M := \<acute>N; \<acute>N := \<acute>I .{\<acute>M = b & \<acute>N = a}." by hoare simp text {* It is important to note that statements like the following one can only be proven for each individual program variable. Due to the extra-logical nature of record fields, we cannot formulate a theorem relating record selectors and updates schematically. *} lemma "|- .{\<acute>N = a}. \<acute>N := \<acute>N .{\<acute>N = a}." by hoare lemma "|- .{\<acute>x = a}. \<acute>x := \<acute>x .{\<acute>x = a}." oops lemma "Valid {s. x s = a} (Basic (\<lambda>s. x_update (x s) s)) {s. x s = n}" -- {* same statement without concrete syntax *} oops text {* In the following assignments we make use of the consequence rule in order to achieve the intended precondition. Certainly, the \name{hoare} method is able to handle this case, too. *} lemma "|- .{\<acute>M = \<acute>N}. \<acute>M := \<acute>M + 1 .{\<acute>M ~= \<acute>N}." proof - have ".{\<acute>M = \<acute>N}. <= .{\<acute>M + 1 ~= \<acute>N}." by auto also have "|- ... \<acute>M := \<acute>M + 1 .{\<acute>M ~= \<acute>N}." by hoare finally show ?thesis . qed lemma "|- .{\<acute>M = \<acute>N}. \<acute>M := \<acute>M + 1 .{\<acute>M ~= \<acute>N}." proof - have "!!m n::nat. m = n --> m + 1 ~= n" -- {* inclusion of assertions expressed in ``pure'' logic, *} -- {* without mentioning the state space *} by simp also have "|- .{\<acute>M + 1 ~= \<acute>N}. \<acute>M := \<acute>M + 1 .{\<acute>M ~= \<acute>N}." by hoare finally show ?thesis . qed lemma "|- .{\<acute>M = \<acute>N}. \<acute>M := \<acute>M + 1 .{\<acute>M ~= \<acute>N}." by hoare simp subsection {* Multiplication by addition *} text {* We now do some basic examples of actual \texttt{WHILE} programs. This one is a loop for calculating the product of two natural numbers, by iterated addition. We first give detailed structured proof based on single-step Hoare rules. *} lemma "|- .{\<acute>M = 0 & \<acute>S = 0}. WHILE \<acute>M ~= a DO \<acute>S := \<acute>S + b; \<acute>M := \<acute>M + 1 OD .{\<acute>S = a * b}." proof - let "|- _ ?while _" = ?thesis let ".{\<acute>?inv}." = ".{\<acute>S = \<acute>M * b}." have ".{\<acute>M = 0 & \<acute>S = 0}. <= .{\<acute>?inv}." by auto also have "|- ... ?while .{\<acute>?inv & ~ (\<acute>M ~= a)}." proof let ?c = "\<acute>S := \<acute>S + b; \<acute>M := \<acute>M + 1" have ".{\<acute>?inv & \<acute>M ~= a}. <= .{\<acute>S + b = (\<acute>M + 1) * b}." by auto also have "|- ... ?c .{\<acute>?inv}." by hoare finally show "|- .{\<acute>?inv & \<acute>M ~= a}. ?c .{\<acute>?inv}." . qed also have "... <= .{\<acute>S = a * b}." by auto finally show ?thesis . qed text {* The subsequent version of the proof applies the @{text hoare} method to reduce the Hoare statement to a purely logical problem that can be solved fully automatically. Note that we have to specify the \texttt{WHILE} loop invariant in the original statement. *} lemma "|- .{\<acute>M = 0 & \<acute>S = 0}. WHILE \<acute>M ~= a INV .{\<acute>S = \<acute>M * b}. DO \<acute>S := \<acute>S + b; \<acute>M := \<acute>M + 1 OD .{\<acute>S = a * b}." by hoare auto subsection {* Summing natural numbers *} text {* We verify an imperative program to sum natural numbers up to a given limit. First some functional definition for proper specification of the problem. *} text {* The following proof is quite explicit in the individual steps taken, with the \name{hoare} method only applied locally to take care of assignment and sequential composition. Note that we express intermediate proof obligation in pure logic, without referring to the state space. *} theorem "|- .{True}. \<acute>S := 0; \<acute>I := 1; WHILE \<acute>I ~= n DO \<acute>S := \<acute>S + \<acute>I; \<acute>I := \<acute>I + 1 OD .{\<acute>S = (SUM j<n. j)}." (is "|- _ (_; ?while) _") proof - let ?sum = "\<lambda>k::nat. SUM j<k. j" let ?inv = "\<lambda>s i::nat. s = ?sum i" have "|- .{True}. \<acute>S := 0; \<acute>I := 1 .{?inv \<acute>S \<acute>I}." proof - have "True --> 0 = ?sum 1" by simp also have "|- .{...}. \<acute>S := 0; \<acute>I := 1 .{?inv \<acute>S \<acute>I}." by hoare finally show ?thesis . qed also have "|- ... ?while .{?inv \<acute>S \<acute>I & ~ \<acute>I ~= n}." proof let ?body = "\<acute>S := \<acute>S + \<acute>I; \<acute>I := \<acute>I + 1" have "!!s i. ?inv s i & i ~= n --> ?inv (s + i) (i + 1)" by simp also have "|- .{\<acute>S + \<acute>I = ?sum (\<acute>I + 1)}. ?body .{?inv \<acute>S \<acute>I}." by hoare finally show "|- .{?inv \<acute>S \<acute>I & \<acute>I ~= n}. ?body .{?inv \<acute>S \<acute>I}." . qed also have "!!s i. s = ?sum i & ~ i ~= n --> s = ?sum n" by simp finally show ?thesis . qed text {* The next version uses the @{text hoare} method, while still explaining the resulting proof obligations in an abstract, structured manner. *} theorem "|- .{True}. \<acute>S := 0; \<acute>I := 1; WHILE \<acute>I ~= n INV .{\<acute>S = (SUM j<\<acute>I. j)}. DO \<acute>S := \<acute>S + \<acute>I; \<acute>I := \<acute>I + 1 OD .{\<acute>S = (SUM j<n. j)}." proof - let ?sum = "\<lambda>k::nat. SUM j<k. j" let ?inv = "\<lambda>s i::nat. s = ?sum i" show ?thesis proof hoare show "?inv 0 1" by simp next fix s i assume "?inv s i & i ~= n" then show "?inv (s + i) (i + 1)" by simp next fix s i assume "?inv s i & ~ i ~= n" then show "s = ?sum n" by simp qed qed text {* Certainly, this proof may be done fully automatic as well, provided that the invariant is given beforehand. *} theorem "|- .{True}. \<acute>S := 0; \<acute>I := 1; WHILE \<acute>I ~= n INV .{\<acute>S = (SUM j<\<acute>I. j)}. DO \<acute>S := \<acute>S + \<acute>I; \<acute>I := \<acute>I + 1 OD .{\<acute>S = (SUM j<n. j)}." by hoare auto subsection {* Time *} text {* A simple embedding of time in Hoare logic: function @{text timeit} inserts an extra variable to keep track of the elapsed time. *} record tstate = time :: nat type_synonym 'a time = "\<lparr>time :: nat, \<dots> :: 'a\<rparr>" primrec timeit :: "'a time com \<Rightarrow> 'a time com" where "timeit (Basic f) = (Basic f; Basic(\<lambda>s. s\<lparr>time := Suc (time s)\<rparr>))" | "timeit (c1; c2) = (timeit c1; timeit c2)" | "timeit (Cond b c1 c2) = Cond b (timeit c1) (timeit c2)" | "timeit (While b iv c) = While b iv (timeit c)" record tvars = tstate + I :: nat J :: nat lemma lem: "(0::nat) < n \<Longrightarrow> n + n \<le> Suc (n * n)" by (induct n) simp_all lemma "|- .{i = \<acute>I & \<acute>time = 0}. timeit ( WHILE \<acute>I \<noteq> 0 INV .{2 *\<acute> time + \<acute>I * \<acute>I + 5 * \<acute>I = i * i + 5 * i}. DO \<acute>J := \<acute>I; WHILE \<acute>J \<noteq> 0 INV .{0 < \<acute>I & 2 * \<acute>time + \<acute>I * \<acute>I + 3 * \<acute>I + 2 * \<acute>J - 2 = i * i + 5 * i}. DO \<acute>J := \<acute>J - 1 OD; \<acute>I := \<acute>I - 1 OD ) .{2*\<acute>time = i*i + 5*i}." apply simp apply hoare apply simp apply clarsimp apply clarsimp apply arith prefer 2 apply clarsimp apply (clarsimp simp: nat_distrib) apply (frule lem) apply arith done end